Multinationals, minority ownership and tax-efficient financing structures - Dirk Schindler; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper presents a theory model that simultaneously accounts for the financing decisions and ownership structure in affiliates of multinational firms. We find that affiliates of multinationals have higher internal and overall debt ratios and lower rental rates of physical capital than comparable domestic firms. We also show that affiliates with minority owners have less debt than wholly owned affiliates and a less tax-efficient financing structure. The latter is due to an externality whereby minority ownership dampens the incentive to avoid taxes through the use of internal debt.
Keywords: H25; F23; 330; multinationals; tax-efficient financing structures; minority ownership; Multinationales Unternehmen; Steuerplanung; Kapitalstruktur; Eigentümerstruktur; Theorie